Exploration of Ideological and Political Education in Computer Software Courses for Industrial Design Majors - Zhang, Yuxi (International Journal of Mechanical and Electrical Engineering, 2025)
Course-based ideological and political education, as a key measure to implement the Party's educational policy and fulfill the fundamental task of fostering virtue and nurturing talent in the new era, aims to incorporate value guidance into the main channel of professional course teaching. Deeply integrating the concept of fostering virtue and nurturing talent into the classroom can help students build a solid moral foundation and shape a correct scientific value system. The teaching content of computer software courses is relatively narrow, mainly focusing on technical aspects, with relatively insufficient attention paid to the moral value aspect. Therefore, under the guidance of the course-based ideological and political education concept, professional teachers need to take professional knowledge as the carrier, closely combine with the core values of the times, and organically integrate ideological and political elements into the entire teaching process. Through this approach, the deep integration of professional knowledge imparting and value cultivation can be achieved, reaching the goal of all-round education in engineering professional courses and helping students grow into high-quality talents with both professional technical literacy and moral sentiments.